DEMAND ANALYSIS OF WHITE CRYSTAL SUGAR IN INDONESIA - Cahyaningtyas, Atri; Sugiyanto, Fx.; Ignasiak –Szulc, Aranka (Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This study aims to analyze the impact of white crystal sugar prices, brown sugar prices, tea prices, and income on the demand for white crystal sugar in Indonesia, addressing the ongoing supply deficit caused by inefficiencies in the national sugar industry. As sugar is a staple food in Indonesia, maintaining a stable supply and price is crucial. This research utilizes a quantitative approach through linear regression analysis of panel data, using secondary data from the Central Statistics Agency (BPS) and the Ministry of Agriculture, covering annual data from 34 provinces in Indonesia from 2015 to 2019. The findings reveal that, during this period, the demand for white crystal sugar showed a negative trend, while prices of brown sugar, tea, and income levels exhibited a positive trend. At a 0.05 significance level, all independent variables, except for brown sugar prices, significantly affect white crystal sugar demand. Interestingly, by incorporating the income effect as a control variable, white crystal sugar demonstrates characteristics of Giffen goods, suggesting that higher income does not necessarily reduce its consumption. These findings highlight the unique demand patterns of sugar in Indonesia and imply that policy measures should focus on addressing supply chain inefficiencies to stabilize the sugar market and ensure affordability for the lower-income population.